Burnout and Secondary Traumatic Stress: Impact on Ethical Behaviour - Everall, Robin; Paulson, Barbara (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper discusses the issue of counsellor burnout and secondary traumatic stress (STS) and its potential impact on ethical behavior. Burnout and STS are common outcomes of providing counselling and psychotherapy and may lead to counsellor impairment. A diminished ability to function professionally may constitute a serious violation of the ethical principles and consequently place clients at risk. The commonalities between burnout and STS and the relationship between impaired practice and ethical behavior are outlined. Preventative measures must be implemented to counteract the affects of burnout and STS. Three major avenues of prevention include self monitoring, obtaining supervision, and intervention and support of colleagues. Implications for practice and training are presented.